2019
DOI: 10.1017/s0022377819000758
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Kelvin–Helmholtz and lower-hybrid drift instabilities

Abstract: Boundary layers in space and astrophysical plasmas are the location of complex dynamics where different mechanisms coexist and compete eventually leading to plasma mixing. In this work, we present fully kinetic Particle-In-Cell simulations of different boundary layers characterized by the following main ingredients: a velocity shear, a density gradient and a magnetic gradient localized at the same position. In particular, the presence of a density gradient drives the development of the lower hybrid drift insta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Recent studies have shown the interplay between the LHDI and the KHI from 2D fully kinetic simulations using parameters typical for the magnetopause of Mercury. 51 Depending on the density gradient and velocity shear across the boundary, the LHDI and the KHI can compete for their respective growth. If the density gradient is strong enough, the LHDI disturbs the structure of the shear layer and can even suppress the onset and evolution of the KHI.…”
Section: Lower Hybrid Wavesmentioning
confidence: 99%
“…Recent studies have shown the interplay between the LHDI and the KHI from 2D fully kinetic simulations using parameters typical for the magnetopause of Mercury. 51 Depending on the density gradient and velocity shear across the boundary, the LHDI and the KHI can compete for their respective growth. If the density gradient is strong enough, the LHDI disturbs the structure of the shear layer and can even suppress the onset and evolution of the KHI.…”
Section: Lower Hybrid Wavesmentioning
confidence: 99%
“…In collisionless space plasmas, plasma mixing across the magnetic field lines occurs at small-scale structures, caused by secondary instabilities excited in the rolled-up vortex of KHI, i.e., at a welldeveloped KHI. To understand the momentum and mass transport mechanisms across the velocity-sheared boundary, high-resolution kinetic simulations of KHI have been conducted (Matsumoto and Seki, 2010;Dargent et al, 2019). Some of the previous studies have identified the importance of including electron inertial effects when assessing mass transport mechanisms across the boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…The change in the initial condition largely alters the time evolution of KHI, even in the small and moderate density gradient cases. For example, the usage of the proposed entropy-based model based on the observations will be important for understanding the interplay between KHI and the lower-hybrid drift instability in plasma mixing (Dargent et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, other instabilities, that can build on the free energy available at the magnetopause and compete with the KHI in an asymmetric velocity shear, shall leave a significant electric field fingerprints to be observed by MEFISTO. This is for instance the case of the lower-hybrid drift instability that might build on the strong density gradients at the Hermean magnetopause and reduce or even suppress the development of the KHI (Dargent et al 2019).…”
Section: Foreshock Waves and Structuresmentioning
confidence: 99%